Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2009
DOI: 10.3899/jrheum.090243
|View full text |Cite
|
Sign up to set email alerts
|

C-Reactive Protein Gene Polymorphisms in Disease Susceptibility and Clinical Manifestations of Korean Systemic Lupus Erythematosus

Abstract: Objective.C-reactive protein (CRP) is a sensitive marker of inflammation. It is hypothesized that polymorphism of CRP gene contributes to susceptibility to systemic lupus erythematosus (SLE). We tested this hypothesis by identifying CRP gene polymorphisms in Korean patients with SLE.Methods.Approximately 1.5 kb of CRP promoter region was screened for single nucleotide polymorphism (SNP) using direct sequencing and 3 SNP in CRP exons by restriction fragment length polymorphism. The basal levels of CRP were meas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
18
0
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 24 publications
2
18
0
1
Order By: Relevance
“…However, we reported there is little or no increase in CRP levels in non-infectious inflammation of SLE (Suh et al 2001(Suh et al , 2006. Additionally, we found that a -390 C>A or T polymorphism within the CRP promoter region might be involved in the regulation of CRP expression and the susceptibility of SLE in Koreans (Kim et al 2009a). CRP is also known to bind to FcγRs (Stein et al 2000).…”
Section: Introductionmentioning
confidence: 82%
“…However, we reported there is little or no increase in CRP levels in non-infectious inflammation of SLE (Suh et al 2001(Suh et al , 2006. Additionally, we found that a -390 C>A or T polymorphism within the CRP promoter region might be involved in the regulation of CRP expression and the susceptibility of SLE in Koreans (Kim et al 2009a). CRP is also known to bind to FcγRs (Stein et al 2000).…”
Section: Introductionmentioning
confidence: 82%
“…Interestingly, the relative induction of CRP expression tends to be more pronounced in tumors with -286 C>A somatic mutation ( Figure 1E), suggesting that this mutation enhances CRP transcription. Indeed, CRP promoter construct carrying the -286 A allele shows higher luciferase reporter activity than the wild-type construct [8].…”
mentioning
confidence: 99%
“…First, we did not explore the physiologic significance of the CRP polymorphism, which we believe has been adequately tested in previous studies (18)(19)(20). Furthermore, at least five other SNPs of the CRP gene may have minor effects on serum CRP level (20,30,(42)(43)(44)(45)(46). Because of the limitations in the original study design, we did not investigate other SNPs of the CRP gene.…”
Section: Discussionmentioning
confidence: 99%